High incidence of radiation-induced brain necrosis in the periventricular deep white matter: stereotactic radiotherapy for brain metastases using volumetric modulated arc therapy - Takayuki Ohguri; Hirohide Itamura; Subaru Tani; Eiji Shiba; Junkoh Yamamoto (Radiation Oncology)
Abstract Purpose In this retrospective study, we aimed to evaluate the efficacy and incidence of radiation-induced brain necrosis (RBN) after volumetric modulated arc therapy-based stereotactic irradiation (VMAT-STI) for brain metastases. Methods In the 220 brain metastatic lesions included between January 2020 and June 2022, there were 1–9 concurrently treated lesions (median 1). A biologically effective dose (BED)10 of 80 Gy and a reduced BED10 of 50 Gy were prescribed to the gross tumor volume (GTV) and planning target volume (PTV) (PTV = GTV + 3 mm) margins, respectively. The number of fractions was adjusted from 3 to 15 to accommodate different GTV sizes; for larger tumor volumes, this was increased while maintaining the BED10 values comparable to those for GTV and PTV margins. Results Of the total patients, 16 (7%) exhibited locally progressive lesions; local tumor recurrence was observed in 2 (1%) patients, while RBN was noted in 14 (6%) patients. RBN was significantly more prevalent in the deep white matter around the lateral ventricles (DWM-LV) than in other sites, occurring in 9/22 (41%) lesions of metastases in the DWM-LV. The 2-year actuarial incidence risk of developing RBN was significantly higher in the DWM-LV (69%) than at other sites (5%). Conclusion The recurrence rate of brain metastases was low, and the incidence of RBN was lower in tumor sites other than the DWM-LV. However, the frequency of RBN was significantly higher in the DWM-LV region. Additional VMAT-STI-prescribed dose protocols are necessary to reduce RBN incidence in DWM-LVs.